Understanding the dynamics of unassisted group egress - Perez, Gay Jane P.
We create an agent-based cellular automata model of pedestrians' egress from two-exit confinements. The pedestrians are mobile agents assigned with traits that include escape strategy, knowledge of the exit location and mobility. To escape, an agent employs strategy: (1) It chooses its own route independently (non-copying, α = 0), (2) It imitates the actions of its neighbors at all times (blind copying, α = 1), or (3) It either copies or acts independently according to a certain probability that is set by the copying parameter α (0 < α < 1). The knowledge of the exit location, on the other hand, is modeled by the information content β (0 < β < 1). β = 1 corresponds to the highest information content, where the agent knows the exact location of the two exits. For our simulations, we investigate the effects of copying parameter α and information content β on the egress dynamics pedestrians. Finally, agent's mobility is set by the panic threshold ⱷ, such that an agent will only be able to move into its chosen cell if the following condition is satisfied: l + r < b + ⱷ, where l, r, and bare the number of occupied cells on the left, right and back of the agent, respectively.A high value of ⱷ means that the agent has a strong urge to move and eventually leave the room.Whereas, the agent is passive and prefers to remain in its present location when ⱷ = 0. In our simulations, we arbitrarily set ⱷ to a constant value (ⱷ=5) to reduce the number of parameters being investigated in this study. In addition to pedestrians characteristics, we also look at how the evacuation dynamics are affected by the exit configuration and room occupancy.We consider two different exit configurations: (1) The two exits are located on one side of the room, and (2) The two exits are located on opposite sides of the room. We vary the room occupancy by changing the total number of pedestrians that are initially confined in the room. Results of the simulation show that for an isolated agent, evacuation time T is inversely proportional to β. In a highly occupied room (occupancy rate R = 80%) with adjacent exits, agents with β > 0.8 escape more quickly if they employ a mixed strategy of copying and non-copying (0.4 < α 0.6).On the other hand, blind copying (α= 1) gives agents with β ¬< 0.1 a better chance of escaping from the same room.For the same α and R values, opposite exits allow faster evacuation for agents with β < 0.1 due to the likelihood of streaming and the lower probability of exit clogging.Finally, we perform experiments to analyze the merit of prior individual training in unassisted egress using mice that are escaping from a water pool to a dry platform through two adjacent exits. We show that different levels of training received by the mice affect its ability to escape from the water pool as seen in the mice trajectories and evacuation time. An untrained mouse would swim aimlessly, in circles, or along walls causing it to spend more time in water. Through repetition, a mouse eventually learned to escape more efficiently - the evacuation time decreases nonlinearly with repetition but further improvement is limited by animal fatigue. In groups, untrained mice are likely to copy each other blindly causing an inefficient utilization of the two available exits.Trained mice are likely to act independently especially when in small groups. We further show that mice also gained from past group experience,as revealed by low average egress time in individual escape.